Spawn production and cultivation technology for Volvariella volvacea: a perspective - AmirN.F., N.F.; Mohd-Aris, A.; Mohmmad, A.; Abdullah, S.; Yusof, F.Z.; Umor, N.A. (Rynnye Lyan Resources, 2023)
Volvariella volvacea has long been cultivated by farmers, but there are still some limitations to producing high-yielding V. volvacea. Several factors can lead to low yields, including poor substrate utilization and inadequate technology. Therefore, many attempts have been made over the years to improve the biological efficiency of the crop using various approaches. In this review, the existing technologies for yield improvement in V. volvacea production are discussed. This paper also elaborates the current practice including spawn improvement method and cultivation strategy. The smart mushroom house technology equipped with Internet of Things is also presented